Enhancing Remote Work Satisfaction and Performance based on Information and Digital Literacy - Sholikah, Mar’atus; Safitri, Anni (Journal of Office Administration : Education and Practice, 2025)
In the digital transformation era and the widespread adoption of remote work, employees must possess strong information and digital literacy skills. This study aims to examine the effect of information and digital literacy on remote work satisfaction and performance. The study also aims to investigate the mediating role of information literacy in the relationship between digital literacy and remote work performance. This study employed a quantitative research design using a cross-sectional survey approach. A total of 68 remote workers were selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings indicate that both information and digital literacy significantly and positively impact remote work satisfaction and performance. Furthermore, information literacy was found to mediate the effect of digital literacy on remote work performance, suggesting that individuals with higher digital skills are more likely to perform effectively when they can also effectively manage and utilize information. This study contributes a novel perspective by highlighting the dual role of literacy as a foundational and mediating factor in enhancing remote work outcomes. Then, the practical standpoint, the results underscore the importance of organizations investing in literacy development programs to enhance employee satisfaction and productivity in digital environments.